Analisis Bibliometrik Corporate Social Responsibility pada Pangkalan Data ProQuest - Firstnila Putri Alamsyah; Roni Jayawinangun; David Rizar Nugroho; Feri Ferdinan Alamsyah (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
The development of sustainability concept make the implementation of corporate social responsibility more intense. These developments has led to change the topic of corporate social responsibility. The aims of this study are (1) to highlight popular topic about the research of corporate social responsibility, (2) to visualization network mapping between keywords about the research of corporate social responsibility, and (3) to find research opportunities about corporate social responsibility for future. This research used quantitative methods with bibliometric analysis approach using co-occurrence analysis. This research used ProQuest database with 57 scholarly journals as population and seven scholarly journal that fulfil the indicator. The result shows that, based on keywords, the implementation of corporate social responsibility focused on social and environmental issues with external reinforcement.